PERAN METODE PENDIDIKAN ISLAM SEBAGAI FONDASI PEMBINAAN KEPRIBADIAN GENERASI MUDA - Anisa; Andi Nurfadilah; Annisatun Nasfah Nurmarifah; Nur Arrum; Izzatul Fatyah Daulay; Sangkot Abdullah Efendi Harahap (STKIP Subang, 2026)
Islamic education plays a strategic role in shaping the personality of the younger generation amid the challenges of rapid social and cultural change and technological development. Islamic education also plays a central role in shaping a strong personality with noble character and serves as the foundation for moral, intellectual, and spiritual development, as emphasized in the interpretation of the Qur'an. This article aims to examine the role of Islamic education methods as the main foundation in shaping the personalities of the younger generation through a Qur'anic interpretation approach. This study uses a literature review method by analyzing verses of the Qur'an related to education, moral guidance, and the process of human personality formation, then relating them to the views of exegetes and contemporary Islamic education concepts. The results of the study show that Islamic educational methods such as exemplary behavior (uswah), habituation (ta'wīd), advice (mau'izhah), dialogue (hiwār), and spiritual strengthening have a significant contribution in shaping the personality of the younger generation to be faithful, noble, and responsible. Therefore, strengthening Islamic education methods is an urgent need in efforts to nurture the personalities of the younger generation to have Islamic character and positive competitiveness in the modern era.